Análisis del impacto económico por efecto de las clausuras temporales realizadas por el servicio de rentas internas (S.R.I.) en los comercios no obligados a llevar contabilidad, en el periodo fiscal 2012, ubicados en los sectores aledaños a la Universidad Central del Ecuador, orientado a la elaboración de un "Manual de buenas précticas del contribuyente" - Baquero Landeta, Christian David (2014)
This research topic is a document that allows the reader to learn more about the problem of studying about what their obligations and rights as a taxpayer not required to take accounting sector. Taxpayers who are operating around the Central University of Ecuador are small traders looking to meet their basic survival needs have sought greater market without knowledge, which becomes a weakness not only in economic but also in antennas anything that has to do with the tax culture that currently manages in the country. Taxpayers investigated sector neither have greater knowledge of the tax legislation governing Ecuador nor know what the obligations and rights of the Internal Revenue Service under the obligations and rights that are subject to begin generating and boost the economy in the sector. Lack of knowledge in not required to take accounting in tax and accounting issues that the taxpayer has generated SRI often punished and close down their establishments for not complying with the duties, as mentioned by the Tax Act tacitly without exclusion any. It is noteworthy that the taxpayer is not required to maintain accounting records once it has been sanctioned by the SRI has an impact not only social but also generates an economic loss for third parties and for yourself.